1988
DOI: 10.1111/j.1349-7006.1988.tb00019.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PSK on Interleukin‐2 Production by Peripheral Lymphocytes of Patients with Advanced Ovarian Carcinoma during Chemotherapy

Abstract: The effects of PSK on OKT 4/OKT 8 cell ratio, interleukin‐2 (IL‐2) production and expression of IL‐2 receptor were examined in peripheral blood lymphocytes (PBL) from patients with advanced ovarian cancer during the course of chemotherapy. Preoperative levels of OKT 4/OKT 8 cell ratio and IL‐2 production in PBL from patients with advanced ovarian cancer were significantly lower than those in cases of benign ovarian tumor. However, the expression of IL‐2 receptor did not show any significant difference between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1990
1990
1993
1993

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…The analysis of the effect of PSK administration on the subpopulations of the cell phenotypes demonstrated that PSK administration increases the proportion of IL-2 receptor + cells, which is consistent with the results of a previous report [9]. There are two possible mechanisms for this increase in the proportion of IL-2 receptor + cells; one is that the production of IL-2 receptors is stimulated by the administration of PSK, and the other is that IL-2 receptor + cells proliferate after PSK stimulation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The analysis of the effect of PSK administration on the subpopulations of the cell phenotypes demonstrated that PSK administration increases the proportion of IL-2 receptor + cells, which is consistent with the results of a previous report [9]. There are two possible mechanisms for this increase in the proportion of IL-2 receptor + cells; one is that the production of IL-2 receptors is stimulated by the administration of PSK, and the other is that IL-2 receptor + cells proliferate after PSK stimulation.…”
Section: Discussionsupporting
confidence: 91%
“…It has also been reported that intraperitoneally or orally administered PSK induces cytotoxic peritoneal exudate cells and augments the NK cell activity of splenocytes in mice [2,4,21,23]. Other reports have indicated that the administration of PSK increases the production of IFN and IL-2 by lymphocytes, which may explain the augmenting effect of PSK on the cytotoxicity of lymphocytes [9,10]. Other mechanisms must also be responsible.…”
Section: Discussionmentioning
confidence: 96%
“…One is a protein-bound polysaccharide (PSK or Crestin) from the mycelium of Coriofus uersicolor (Hosokawa et a f . , 1986) which has already been used clinically (Kikuchi et al, 1988) in Japan and another is a glucan (named Lentinan) from the fruit bodies of Lentinus edodes (Chihara et al, 1970;Maeda et al, 1988;Baba et al, 1986). Ohmori et al (1986) reported that these antitumour polysaccharides were markedly effective against allogeneic tumours, however, they were scarcely effective against syngeneic tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with cimetidine significantly increased the helper:suppressor ratios but IL-2 receptors remained unchanged. 29 CIMETIDINE IN PATIENTS WITH CANCER Impaired cell-mediated immune response is commonly seen in patients suffering from a variety of malignancies. 17 • 3O Richtsmeier and Eisele studied the effect of cimetidine on ten untreated patients with squamous cell carcinoma of the head and neck.…”
Section: Effects Of Cimetidine On Subpopulations Of Lymphocytes and Imentioning
confidence: 99%